1998
DOI: 10.1007/bf02462906
|View full text |Cite
|
Sign up to set email alerts
|

High school laboratory work in Western Australia: Openness to inquiry

Abstract: Laboratory work has always been the most distinctive feature of secondary science teaching and learning. With the increasing emphasis on student centred learning and the importance of developing investigation and problem-solving skills there is value in reflecting on the type of laboratory work that is carried out in the science curriculum. The purpose of this study was to determine the nature of the laboratory work undertaken by lower secondary science students, and in particular, to determine the openness to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 8 publications
1
19
0
4
Order By: Relevance
“…The inquiry levels in the physics practical examinations were restricted to structured and confirmation inquiry levels, with the former dominating. To a large extent the findings in this study are similar to those reported in previous studies that examined science textbooks and laboratory manuals (Tamir & Luneta, 1981;Staver & Bay, 1987;Pizzin, Shepardson, & Abell, 1991) and laboratory manuals (Friedler & Tamir, 1986;Germann, Haskins & Auls, 1996;Staer, Goodrum & Hackling, 1998). However, there is some consistency in the coverage of inquiry skills in the syllabus and practical examinations.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
“…The inquiry levels in the physics practical examinations were restricted to structured and confirmation inquiry levels, with the former dominating. To a large extent the findings in this study are similar to those reported in previous studies that examined science textbooks and laboratory manuals (Tamir & Luneta, 1981;Staver & Bay, 1987;Pizzin, Shepardson, & Abell, 1991) and laboratory manuals (Friedler & Tamir, 1986;Germann, Haskins & Auls, 1996;Staer, Goodrum & Hackling, 1998). However, there is some consistency in the coverage of inquiry skills in the syllabus and practical examinations.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
“…As Welch et al (1981) suggested, inquiry teaching should take contextual reality of the school setting into consideration. We think applying 2b guided inquiry teaching (Staer et al, 1998) can fit with Taiwanese science teachers' concerns: meeting with the curriculum standard, filling the content information, helping students promote to better performance and dealing with large class sizes of around 35 students per class.…”
Section: Science Inquirymentioning
confidence: 97%
“…Finally for level 3, the teacher provides only learning environment for students to generate inquiry question, procedures and solutions for themselves. Staer, Goodrum and Hacking (1998) modified Hegarty-Hazel's (1986) above levels and added lab equipments into the category. They further classified level 2 into 2a and 2b.…”
Section: Science Inquirymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous scholars (i.e., Hackling & Garnett, 1995;Lin et al, 2014;Luft, 2001;Staer, Goodrum, & Hackling, 1998;) have indicated that the cultivation of students" inquiry abilities should be at the center of contemporary science education. Therefore, providing students with active opportunities to inquire and receive relevant training during the teaching process has become an essential instructional activity.…”
Section: Scientific Inquiry As An Approach In Science Teachingmentioning
confidence: 99%